Differential sensitivity of durum wheat, barley and oat to pyroxasulfone (Semiárida, 2026)
Durum wheat, barley, and oats are regionally important crops in Argentina, and unlike major cereals, few herbicides are registered for weed control, particularly for grass species. The objective of this study was to determine whether interspecific variation in sensitivity to the herbicide pyroxasulfone exists among durum wheat, barley, and oats. Herbicide response was evaluated through plumule growth assays in Petri dishes, pot experiments in a growth chamber, and field trials. A total of 15 durum wheat varieties, 11 barley varieties, and 11 oat varieties were assessed under different pyroxasulfone doses. Glutathione S-transferase (GST) enzymatic activity was quantified as a detoxification mechanism potentially involved in differential sensitivity. Across all experimental approaches, oats consistently showed the greatest sensitivity to herbicide, exhibiting significantly lower relative growth than the other two cereals. In most experiments, barley was less sensitive to pyroxasulfone than durum wheat. GST activity results indicated that greater herbicide sensitivity was associated with higher enzymatic activity rates. Under field conditions, rainfall was a key factor influencing crop response to pyroxasulfone; across the wide germplasm evaluated, the findings highlight the need to consider multiple variables for the safe and effective use of pyroxasulfone in agricultural systems.
Keywords: residual herbicide; minor cereals; winter cereals